Efektivitas Pengawasan oleh DLHK dalam Mengawasi Kegiatan Perusahaan terhadap Dampak Kesehatan Masyarakat berdasarkan Undang-Undang No. 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Fajar Abdul Aziz; Sartika Dewi; Muhamad Abas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to determine the effectiveness of supervision conducted by the Environmental and Sanitation Agency (DLHK) of Karawang Regency regarding the mining activities of PT Mas Putih Belitung based on Law Number 32 of 2009 concerning Environmental Protection and Management. The study also examines the obstacles faced in monitoring the impacts of mining activities on public health and the environment. The research used an empirical juridical method with legislative and empirical approaches. Data were collected through interviews, observations, and literature studies, then analyzed qualitatively using Soerjono Soekanto’s theory of legal effectiveness. The findings show that DLHK supervision has been implemented but has not yet operated effectively. Several factors contribute to this condition, including limited human resources, inadequate facilities and infrastructure, weak administrative law enforcement, low community participation, and insufficient compliance by the company in environmental management practices. Therefore, stronger supervision, improved law enforcement, and greater collaboration between government, companies, and communities are necessary to ensure environmental protection and public health sustainability.